الذكورية ونموذج البطولة في رواية المسرات والأوجاع - عبد الله م.م. كفاح حسين (Tasnim International Journal for Human, Social and Legal Sciences, 2022)
The novel of (Delights and Aches) is a great and significant work in Arabic literature. We are in front of a novel that is the most mature and complete of contemporary Arab literature. It is different from the previous novels of Al-Takarli. It is an independent world in itself. This novel, through its 500 pages, provides us with the essence of fiction art and the origins of its worlds.